Thought complements in Australian languages. (July 2021) - McGregor, William B.
Abstract: Very little has been written on the grammar of complement constructions in Australian Aboriginal languages. Grammars rarely provide much information, and few references treat the topic either in particular languages or cross-linguistically. This paper addresses this lacuna with a typological investigation of thought complements in the languages of the continent. Some languages show evidence of a separate construction type for coding propositional thoughts. In most Australian languages it seems that a limited range of verbs can be employed in the matrix clause; these usually include generic verbs meaning 'say, do, think' or 'hear, think'. Two other constructions resemble the reported thought construction, a type of desiderative, and mistaken belief constructions; the major grammatical features of these constructions are discussed. In most languages there is no compelling evidence that the clause of thought serves as an argument of the matrix clause, and thus the construction is not a complement construction in the traditional sense. Rather, what is involved is framing – a relation distinct from both embedding and dependency; some issues with this analysis are discussed and resolved. The investigation is based on a corpus of just over seventy languages, partly a convenience sample (depending on available information) and partly a representative one (the major geographical regions and families are included, albeit unevenly). Highlights: A limited number of verbs of thought frame complements in Australian languages. Most common matrix verbs are generic, meaning 'say, do, think' and 'hear, think'. Desideratives are sometimes represented in the manner of thought complements. A distinct mistaken belief construction is found in many Australian languages. An analysis in terms of framing and/or scope is plausible and accounts for the meaning of thought complements.